Strategi Kepala Balai Latihan Kerja Komunitas (BLKK) Bidang Teknologi Dan Informasi Dalam Meningkatkan Sumber Daya Manusia Di Pondok Pesantren Modern Minhajul Muttaqin - Imron Rosadi; Akhsanul Huda; Agus Siswanto (Idaarotul Ulum, 2025)
This research is motivated by the author's interest in the Strategy of the Head of the Community Work Training Center (BLKK) in the Technology and Information Sector in improving Human Resources at the Minhajul Muttaqin Modern Islamic Boarding School. Meanwhile, current education has at least three dimensions of skills, including: work skills and survival along with life skills, learning skills and innovation, and information technology and media skills. This type of research is qualitative using a descriptive approach with data collection obtained through observation, interviews and documentation. In testing the validity of the data using data triangulation techniques. While data analysis techniques include data reduction, data display, drawing conclusions and verification. The results of this study indicate that the human resource development strategy at the BLKK of the Minhajul Muttaqin Modern Islamic Boarding School is through a graphic design training program for students, employees and the community around the Islamic boarding school with a facilitative training strategy. BLKK has carried out training quite well starting from, (1) Planning a skills development strategy that has prepared the needs of the training program using funds from the Republic of Indonesia's employment in accordance with the requirements and functions of the Work Training Center. However, the long-term program planning of BLKK has not been planned in a structured manner. (2) The implementation of the graphic design program strategy that is applied consists of three programs (competency units, support groups and on the job training (OJT), with the application of the material in training, it is able to develop skills specifically in graphic design. However, the implementation of the training has not been maximized, this can be seen from the obstacles experienced. (3) Evaluation of the training program strategy has an impact on participants, especially graphic design skills and work discipline. The evaluation of the training program is in the form of an evaluation report prepared by the manager as a report to the Serang Vocational Training Development Center (BBPVP).